"y'=\\sum_{k=0}^\\infty A_k(k+r) x^{k+r-1}"
"y''=\\sum_{k=0}^\\infty A_k (k+r)(k+r-1)x^{k+r-2}"
"x^2\\sum_{k=0}^\\infty A_k (k+r)(k+r-1)x^{k+r-2}+"
"(4x-x^2)\\sum_{k=0}^\\infty A_k(k+r) x^{k+r-1}+"
"(2-x)\\sum_{k=0}^\\infty A_k x^{k+r}="
"\\sum_{k=0}^\\infty (A_k (k+r)(k+r-1)+4A_k(k+r)+2A_k)x^{k+r}-"
"-\\sum_{k=0}^\\infty A_k(k+r+1)x^{k+r+1}="
"\\sum_{k=0}^\\infty A_k((k+r)(k+r-1)+4(k+r)+2)x^{k+r}-"
"-\\sum_{k=1}^\\infty A_{k-1}(k+r)x^{k+r}="
"[(k+r)(k+r-1)+4(k+r)+2="
"k^2+2kr+r^2-k-r+4(k+r)+2="
"(k+r)^2+3(k+r)+2=(k+r+1)(k+r+2) ]"
"A_0(r+1)(r+2)x^r+\\sum_{k=1}^\\infty(A_k(k+r+1)(k+r+2)-A_{k-1}(k+r))x^{k+r}"
indicial polynom:
"(r+1)(r+2)=0,r_1=-1,r_2=-2""A_k(k+r+1)(k+r+2)-A_{k-1}(k+r)=0"
"A_k(k+r+1)(k+r+2)=A_{k-1}(k+r)""case 1: k=1,r=-2"
"A_1(1-2+1)(1-2+2)=A_0(1-2)"
"A_0=0,A_k=0;""y = 0"
"A_1(1-1+1)(1-1+2)=A_0(1-1) = 0"
"A_0\\not = 0 , A_1=0,A_2=0,..."
"y=\\frac{A_0}{x}; y = \\frac{0}{x}=0, when A_0=0."
Answer: y=A0/x, A0 is real number.
Comments
Leave a comment